An innovative air-cooling system for efficiency improvement of retrofitted rooftop photovoltaic module using cross-flow fan - Mustafa, Rozita; Mohd Radzi, Mohd Amran Bin; Hizam, Hashim Bin; Che Soh, Azura (Center of Biomass & Renewable Energy (CBIORE), 2024)
This study presents an innovative air-cooling photovoltaic (PV)system using cross-flow fan with speed regulation to optimize performance of rooftop PVsystem in tropical climates like Malaysia. Air passed through the impeller enters perpendicularly to the motor shaft, deflected by the fan blades and evacuated, allowing the fan to operate at its most efficient operating point. The airflow provided within the rear of the PV modules and the roof surface blow out the trapped hot air. Changes in the module temperature (Tcell) are detected and the fan speed are adjusted accordingly to the PWM. This method was tested for 12 hours continuously from 7:00 am on the existing PV system at German Malaysian Institute (GMI) Bangi. The highest Tcell achieved 72.88 °C and 55.75°C without and with air-cooling system with average power 210.22 W and 246.67 W per peak sun factor (PSF) respectively. There was a 17.34% increase in average power with a 13.18% in average net output power and achieved 6.68% energy efficiency using the proposed cooling system. Tcell increases more swiftly and reaches higher temperatures in the absence of a cooling system, whereas Tcell increases more slowly and at lower temperatures when a cooling system is present. The projected system's power rating was 6.48 W, which is 2.6% per PV module, and it really attained 6.32 W, which is 2.53% per PV module, while total energy consumption by the fan was 51.89 Wh per day, which is only 3.89% per PV module.